Genre Trouble and History's Miseries in Colson Whitehead's The Underground Railroad. (25th April 2019) - Li, Stephanie
Abstract: The Underground Railroad (2016) is, like all of Colson Whitehead's work, a genre troublemaker. Much of this instability derives from Whitehead's approach to history. He offers a problematic if expansive vision of inequality and its evolution. By presenting diverse portraits of black subjection with anachronistic references, Whitehead demonstrates that chattel slavery is just one expression of white supremacy. However, even as Whitehead upends expectations of fantasy to expose certain features of history, I argue that this is not a redemptive history but rather one mired in the demands of the literary marketplace and an author uniquely attuned to what audiences are willing to bear. Notions of truth and history are necessarily fraught terms in contemporary narratives of slavery. However, Whitehead betrays his own self-defined conception of the psychological truth possible in depictions of slavery in order to conform to familiar expectations of narratives about enslavement. Even as it explodes generic categories, The Underground Railroad quaintly resolves its own genre trouble by offering a dangerously performative conception of history, an inexplicably moral protagonist, and a happy ending that panders to audience appetites involving tales of black suffering.